Immunopathogenesis of severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2) infection: a concise update - Dewi, Shinta Trilaksmi; Soebono, Hardyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus which has been identified as the cause of the recently emerging coronavirus disease 2019 (COVID-19), a respiratory-related infectious disease, in late 2019. As of May 2020, SARS-CoV-2 has infected millions of people with almost 300.000 deaths worldwide only within few months since its first case was reported. While this infection mostly results in mild diseases, the increasing number of severe cases and deaths cannot be overlooked. Due to its novelty, many facets of SARS-CoV-2 pathogenesis are not well understood. This review presents updated knowledge on the key virus characteristics of SARS-CoV-2 and critical notes in the pathogenesis of this viral infection in human that is currently proposed to largely involve various aspects of the host immune responses. While the immediate impact of viral infection in the target cells contributes to the development of the disease, the ability of the virus to modify the host responses may result in the dysregulation of innate and adaptive immune responses, which commonly manifest in the severe spectrum of the disease. Having deep understanding on this complex process is central for tailoring appropriate management for the infected patients as well as for developing effective preventive measures, most importantly vaccine, which is hoped to occur in the near future.